2010
DOI: 10.1017/s0967199409990384
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant treatment during preservation of bovine ovaries increased the development potential of embryos

Abstract: The overnight preservation of bovine ovaries would be highly useful in the subsequent harvest of viable oocytes for reproductive study. The present study aimed to optimize conditions for overnight preservation of bovine ovaries by examining the effects of temperature, solution and supplementation. In Experiment 1, the rate of development to the blastocyst stage of oocytes derived from ovaries preserved at 15°C was higher than that at either 5 or 25°C (p < 0.05). In Experiment 2, the rate of development to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The ovaries were maintained at 15–20 C and transported to the laboratory in a saline solution supplemented with antibiotics and antimycotics (AB; Invitrogen, Carlsbad, CA, USA); the time between recovery of ovaries and transport to the laboratory was approximately 1 h. The ovaries were then held in saline supplemented with 0.3 mM reduced glutathione (GSH; G4251, Sigma-Aldrich, St. Louis, MO, USA) and 1% AB at 15 C for 20 h with shaking [17]. …”
Section: Methodsmentioning
confidence: 99%
“…The ovaries were maintained at 15–20 C and transported to the laboratory in a saline solution supplemented with antibiotics and antimycotics (AB; Invitrogen, Carlsbad, CA, USA); the time between recovery of ovaries and transport to the laboratory was approximately 1 h. The ovaries were then held in saline supplemented with 0.3 mM reduced glutathione (GSH; G4251, Sigma-Aldrich, St. Louis, MO, USA) and 1% AB at 15 C for 20 h with shaking [17]. …”
Section: Methodsmentioning
confidence: 99%
“…2 effective use of the oocytes contained within [6]. The type of transportation medium [3,[6][7][8], storage time [3][4][5][6][7][8][9][10][11][12][13][14][15][16], as well as, its temperature during transportation of the ovaries [4,5,[10][11][12][13][14][15][16] are among the factors affecting subsequent follicular and oocyte survival, and oocyte developmental competence [7]. Consequently, many studies have been conducted in order to improve oocyte preservation by modifying the transportation solutions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The main goal in ovaries preservation is to maintain the function of the oocyte enclosed in follicle for in vitro maturation and fertilization. Accordingly, many studies investigated the effects of different antioxidants to reduce the damage caused by free oxygen radicals during ovaries preservation [6][7][8]15]. Several studies indicated that the imbalance between ROS production and antioxidant activities could cause oxidative stress [7,23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the largest outstanding problems associated with this technique is our current lack of knowledge concerning the effect of sperm capacitation and motility upon the subsequent development of injected oocytes. We have previously demonstrated that the methyl-β-cyclodextrin induced capacitation of sperm promoted fertilization in vitro [1]. We showed that single activated sperm caught could be caught us- …”
Section: Editorialmentioning
confidence: 92%